Swimming Against the Current: Contrarian Retail Trading - Cannon, Brad; Mohrschladt, Hannes (Journal of Financial and Quantitative Analysis, 2026)
Abstract Retail investor contrarian selling depends on whether a position is at a gain or a loss. Selling propensity increases in daily returns for positions with unrealized gains (contrarian selling) and decreases in returns for loss positions (trend-following selling). This pattern is consistent with behavioral arguments that investors update their beliefs when stock prices move away from their purchase prices. In line with increased liquidity from contrarian selling, illiquid stocks exhibit weaker short-term reversals when investors have higher unrealized capital gains. Our findings diminish following stock splits, suggesting that unrealized capital gains are central to contrarian behavior, particularly when investors perceive them clearly.